Condition of child labour in restaurant - Tripathi, Sakuntala (Patan Prospective Journal, 2023)
This research study was carried out to reflect Child Labourer's condition in Restaurants of Sundhara which is situated in Kathmandu Metropolitan city. This study is focused on child labourers in restaurants of Sundhara. Till date nobody has made it a research area to carry out a child labourer's condition. Both descriptive and analytical research design has been used in this research. The initiative has been taken to include both qualitative and quantitative data statistics in the research. In this study, data were collected by using purposive sampling method of child labour worked in Restaurants Kathmandu Metropolitan city Sundhara. 30 Child labourers have been involved for the research. Both primary and secondary data has been collected for the study. The collected data has been presented in tabulated from data obtained in numeric form have been presented with number and percentage forming a table and data which are not obtained in numeric form have been presented in descriptive way. The sector of child labour in Nepal basically in Sundhara, Kathmandu the situation of child labourers was found so pathetic. Children are working in poor condition without having proper food, proper place to stay and sleep no rest while working and more above that children are not getting any education for their bright future. Though there are lots of NGOs and INGOs working in the child sector but the situation of children is not progressive way.